Molecular detection and antimicrobial resistance of Klebsiella pneumoniae from house flies (Musca domestica) in kitchens, farms, hospitals and slaughterhouses - Reza Ranjbar; Morteza Izadi; Taghi T. Hafshejani; Faham Khamesipour (Elsevier, 2016)
Summary: Identifying disease vectors and pathogens is one of the key steps in controlling vector-borne diseases. This study investigated the possible role of house flies (Musca domestica) as vectors in the transmission of Klebsiella pneumoniae in Chaharmahal VA Bakhtiari and Isfahan provinces of Iran. House flies were captured from household kitchens, cattle farms, chicken farms, animal hospitals, human hospitals and slaughterhouses. Isolation of K. pneumoniae from external surfaces and guts of the flies was performed using MacConkey agar (MA) and thioglycollate broth (TGB). Identification of the isolates was performed with phenotypic techniques and polymerase chain reaction (PCR). A total of 600 house flies were sampled during the study period from different locations in four different seasons. Overall, 11.3% of the captured house flies were positive for K. pneumoniae. In Chaharmahal VA Bakhtiari province, the prevalence was 12.7%, while in Isfahan province, 10.0% of the sampled house flies were infected with K. pneumoniae. Season-wise, the highest prevalence of infections among the house flies was in summer. The organisms were highly resistant to ampicillin, amoxicillin, cefotaxime and piperacillin. A lowest level of resistance was observed for imipenem/cilastatin. The findings of this study demonstrated that house flies are potential vectors of antibiotic-resistant K. pneumoniae in Isfahan and Chaharmahal provinces, Iran. Control efforts for infections caused by this particular bacterium should take M. domestica into account. Keywords: Klebsiella pneumoniae, Musca domestica, Nosocomial infections, Vector-borne diseases